Cognitive Functioning and Associated Factors in Older Adults: Results from the Indonesian Family Life Survey-5 (IFLS-5) in 2014-2015. (3rd February 2019) - Pengpid, Supa; Peltzer, Karl; Susilowati, Indri Hapsari
Abstract : Objective . The study aims to investigate cognitive functioning and associated factors in a national general population-based sample of older Indonesians. Methods . Participants were 1228 older adults, 65 years and older (median age 70.0 years, Interquartile Range=6.0), who took part in the cross-sectional Indonesian Family Life Survey-5 (IFLS-5) in 2014-15. They were requested to provide information about sociodemographic and various health variables, including cognitive functioning measured with items from the Telephone Survey of Cognitive Status (TICS). Multivariable linear regression analysis was performed to assess the association of sociodemographic factors, health variables, and cognitive functioning. Results . The overall mean cognition score was 14.7 (SD=4.3) (range 0-34). In adjusted linear regression analysis, older age, having hypertension, and being underweight were negatively associated with better cognitive functioning and higher education was positively associated with better cognitive functioning. Conclusion . Several sociodemographic and health risk factors for poor cognitive functioning were identified which can guide intervention strategies in Indonesia.